2023
DOI: 10.3390/biology12050702
|View full text |Cite
|
Sign up to set email alerts
|

A Novel In Vivo Active Pemphigus Model Targeting Desmoglein1 and Desmoglein3: A Tool Representing All Pemphigus Variants

Abstract: Background: Pemphigus is a life-threatening blistering autoimmune disease. Several forms, characterized by the presence of autoantibodies against different autoantigens, have been described. In Pemphigus Vulgaris (PV), autoantibodies target the cadherin Desmoglein 3 (DSG3), while in Pemphigus foliaceous (PF) autoantibodies target the cadherin Desmoglein 1 (DSG1). Another variant, mucocutaneous Pemphigus, is characterized by the presence of IgG against both DSG1 and DSG3. Moreover, other forms of Pemphigus char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous studies demonstrated that antibodies induced by immunization with rDsg3 in wild‐type mice, constrained by immune tolerance, failed to produce pathogenic antibodies capable of recognizing native Dsg3 15–18 . Notably, the adjuvants used in these studies were complete Freund's adjuvant (CFA), alum, 15,17,19 squalene‐based TiterMax 18 or unspecified 11 . Although CFA based on mycobacteria remains the most potent immunopotentiator reported to date, 20 we believe that the recent availability of vaccine adjuvants with excellent immune‐activation capabilities opens up possibilities for inducing Dsg3‐specific autoimmune responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that antibodies induced by immunization with rDsg3 in wild‐type mice, constrained by immune tolerance, failed to produce pathogenic antibodies capable of recognizing native Dsg3 15–18 . Notably, the adjuvants used in these studies were complete Freund's adjuvant (CFA), alum, 15,17,19 squalene‐based TiterMax 18 or unspecified 11 . Although CFA based on mycobacteria remains the most potent immunopotentiator reported to date, 20 we believe that the recent availability of vaccine adjuvants with excellent immune‐activation capabilities opens up possibilities for inducing Dsg3‐specific autoimmune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a clear need exists for novel PV animal models that exhibit overactivated yet controllable immune responses, addressing these limitations and providing a more comprehensive understanding of PV pathogenesis and the development of therapeutic interventions. Previous studies demonstrated that antibodies induced by immunization with rDsg3 in wild‐type mice, constrained by immune tolerance, failed to produce pathogenic antibodies capable of recognizing native Dsg3 15–18 . Notably, the adjuvants used in these studies were complete Freund's adjuvant (CFA), alum, 15,17,19 squalene‐based TiterMax 18 or unspecified 11 .…”
Section: Introductionmentioning
confidence: 99%